In‐depth structural and chemical characterization of engineered TiO2 films. (10th February 2016) - Ortel, Erik; Häusler, Ines; Österle, Werner; Narbey, Stéphanie; Oswald, Frédéric; Andersen, Inge H.; Holzweber, Markus; Unger, Wolfgang E. S.; Hodoroaba, Vasile‐Dan
Abstract : Analytical routines for a comprehensive in‐depth morphological, structural, and chemical characterization of functionalized TiO2 films by using different state‐of‐the‐art analytical techniques are presented and discussed with the main objective to identify potential reference TiO2 coating parameters able to be certified at a later stage. TiO2 films fabricated by two different synthetic procedures as representative for two main large‐scale applications were selected: (i) pulsed d.c. magnetron sputtering for photocatalytic applications and (ii) screen printing from preformed anatase nanoparticles. The screen‐printed films were further loaded with a sensitizing dye for application as a dye‐sensitized solar cell. Film properties such as microstructure and crystallographic texture of pulsed d.c. magnetron sputtering synthesized films were systematically studied by means of scanning nanobeam electron diffraction in a transmission electron microscope and the surface and inner morphology by scanning electron microscopy. The dye distribution over the depth of screen‐printed TiO2 layers was analyzed before and after dye‐loading by means of energy dispersive X‐ray spectroscopy at scanning electron microscope, Auger electron spectroscopy and time‐of‐flight secondary ion mass spectrometry. The long‐term goal of the present study is the improvement of quality of the TiO2 film parameters as measured by using different types of reference TiO2 coatings having specific parameters certified. Copyright © 2016 John Wiley & Sons, Ltd.